The Short Stories of John Joseph Mathews, an Osage Writer - Mathews, John Joseph, 1895-1979 (Book collections on Project MUSE., 2022)
"Susan Kalter presents seventeen previously unpublished short stories of John Joseph Mathews and skillfully intertwines literary analysis, author biography, and archival research from the short stories themselves with Mathews's journals and personal correspondence"--